(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2022)
The text is a review of a book Branko Mikulić-Political Biography 1964–1989, by Dr. Sc. Dženita Sarač-Rujanac, Institute of History, Sarajevo 2020.